Longitudinal evidence of technology-enhanced, individualized neuromotor rehabilitation on autonomy, cognition, quality of life, and psychological well-being: Pilot multi-sample study - Francesco Zanatta; Patrizia Steca; Cira Fundarò; Anna Giardini; Chiara Ferretti; Giovanni Arbasi; Roberta Adorni; Marco D’Addario; Antonia Pierobon (PLoS ONE, 2026)
Background Over the last decades, neuromotor rehabilitation programs have integrated multidisciplinary approaches with the implementation of emerging technology (e.g., robotics and virtual reality – VR), to effectively target recovery complexity. While this strategy supported patient’s physical improvement, little evidence has been reported regarding the widespread effects on non-motor rehabilitation outcomes. Methods A prospective, two-arm, non-randomized study design was adopted to provide pilot feasibility evidence on the multi-domain impact of personalized technology-enhanced neuromotor rehabilitation from convenience sub-samples of patients with stroke, Parkinson’s Disease (PD), and osteoarthritis (OA). Technological intervention consisted of the integrated use of robot-assisted and/or VR-based exercises, individualized based on patient’s diagnosis and rehabilitation goals. Study outcomes included patient’s functional status (autonomy in ADLs, risk of falls), cognition (attention and executive functions, memory, verbal fluency), physical and mental health-related quality of life (HRQoL), and psychological status (anxiety and depression symptoms, and well-being) and were compared to patients participating in standard training only. Rehabilitation experience and technology psychosocial impact were also evaluated. Intra- and intergroup comparisons along with general linear models were statistically tested within each sub-sample considered independently over three timepoints (baseline, post-intervention, 6-month follow-up). Results At post-intervention, significant multi-domain intra-group improvements were observed within each sub-sample. Between-group differences were found on ADLs autonomy (stroke and PD; p < .05), executive functions (stroke; p < .01), anxiety and depression (OA and PD, respectively; p < .05), and well-being (stroke and OA; p < .05). Interaction effects (time x group) were significant only on well-being variables in stroke ( p = .01) and OA ( p = .02), evidencing wider short-term effects of technology-enhanced programs compared to standard training. At 6-month, significant time effects indicating sustained improvements over the three timepoints were estimated on HRQoL within each sub-sample ( p < .05) and, additionally, on anxiety and depression in stroke ( p = .02) and OA ( p < .001). Interaction effects emerged only on physical HRQoL in OA ( p = .02), along with significant between-group differences on HRQoL and anxiety and depression in OA ( p < .05) and PD ( p = .01), respectively. Conclusion Further full-scale trials are warranted to confirm the longitudinal trends observed in this pilot study and to further investigate the potential multi-domain benefits of multidisciplinary and technology-integrated recovery approaches across different clinical populations. Trial registration ClinicalTrials.gov ID: NCT05399043 .